A NEW CAD SOFTWARE FOR EVALUATION OF BREAST LESIONS IN CONTRAST –ENHANCED MR MAMMOGRAPHY: Pharmaceutical Sciences-Medicine - HOSEIN BAHREYNI-TOSSI, MOHAMMAD; SADEGHI MOGHADAM, MAJID; NEKOOIE, SIROUS (International Journal of Life Science and Pharma Research, 2018)
The aim of this study was software designing for the detection and diagnosis of breast lesions in contrast enhanced MR mammography. In this study MR mammography was performed in 31 women with 54 suspected breast lesions consisting of 34 malignant and 20 benign entities. Every lesion was evaluated through multiple diagnostic parameters such as morphologic and physiologic lesion traits by designed software. Final results from the physiologic and morphologic assessments for each lesion were compared with the pathology reports. Designed software could show easy reading colored view of each image and it was able to show the margin and internal architecture of lesions. Final results showed that software sensitivity for lesion detection was 94.1% and its specificity was 85%. In this study, efforts have been made to design software for the assessment of physiologic and morphologic breast lesion traits simultaneously. Relatively high sensitivity and specificity is due to this contemporary assessment.